2023
DOI: 10.1530/eor-22-0103
|View full text |Cite
|
Sign up to set email alerts
|

Lateral hinge fracture in medial opening wedge high tibial osteotomy: a narrative review

Abstract: Lateral hinge fractures (LHF) are one of the most common complications of medial opening wedge high tibial osteotomy (MOWHTO), and are the leading cause of construct instability displacement, non-union, and varus recurrence after this procedure. To date, Takeuchi’s classification is the most popular classification to describe this complication, and it can help surgeons to make intra and postoperative decisions. Opening medial gap width is the most recognized factor related to LHF occurrence. Recognizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Achieving optimal medial distraction is essential during MOWHTO surgery, and this is best accomplished by preserving the lateral cortical hinge. The literature has consistently emphasised the importance of protecting a lateral cortical hinge of at least 1 cm during osteotomy [ 3 , 6 , 20 ]. Failing to preserve the lateral cortical hinge can result in instability at the osteotomy site, which may have significant clinical consequences, including loss of correction, impaired postoperative rehabilitation, delayed union, nonunion and implant failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Achieving optimal medial distraction is essential during MOWHTO surgery, and this is best accomplished by preserving the lateral cortical hinge. The literature has consistently emphasised the importance of protecting a lateral cortical hinge of at least 1 cm during osteotomy [ 3 , 6 , 20 ]. Failing to preserve the lateral cortical hinge can result in instability at the osteotomy site, which may have significant clinical consequences, including loss of correction, impaired postoperative rehabilitation, delayed union, nonunion and implant failure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the technical challenges of preserving lateral cortical hinges during MOWHTO procedures, another challenge is recognising LHFs intraoperatively or even postoperatively [ 6 , 16 ]. A recent systematic review reported 40% LHFs in one study, 10% of which were missed using plain radiographs and fluoroscopy [ 15 ].…”
Section: Introductionmentioning
confidence: 99%